The Coronaviruses of Animals and Birds: Their Zoonosis, Vaccines, and Models for SARS-CoV and SARS-CoV2 - Alluwaimi, Ahmed M.; Alshubaith, Ibrahim H.; Al-Ali, Ahmed M.; Abohelaika, Salah (Frontiers in Veterinary Science, 2020)
The viruses of the family Coronaviridae are ubiquitous in nature due to their existence in wide spectrum of mammals and avian species. The coronaviruses as RNA viruses exist as quasispecies because of their high rate of mutations. This review has elaborated the pathogenesis and the developed vaccines of the most of the ubiquitous coronavirus's diseases, mainly bovine, dromedary camel, porcine, feline, canine, and avian coronaviruses. The review has emphasized on the great setback of the full exploitation of the most of the coronavirus’s diseases, which it raised the premonition to the prospect of the effective vaccines to these diseases. The therapeutical trials for the treatment of the SARS-CoV2 and their setbacks were also addressed. The review has drawn the attention to the lessons accumulated from the overwhelming studies of the pathogenesis of animals and birds’ coronaviruses and their vaccines, particularly the bovine, feline and avian coronaviruses. These lessons had immense influence on the approaches to exploit the human coronaviruses pathogenesis and vaccines development. In addition, the extensive efforts to designate suitable animal models to study the lately emerged human coronaviruses were one of the invaluable contributions carried out by the veterinarian scientist. Finally, factors and determinants that contribute to the possibility of emerging new coronavirus zoonotic disease were elaborated and call has been raised to urge the transdisciplinary collaboration in the implementation of the “One Health” concept.